Prospects for the Development of Foreign Trade of Kazakhstan with the Countries of the Regional Comprehensive Economic Partnership - R. T. Dulambayeva; G. D. Yessenzholova (Экономика: стратегия и практика, 2022)
The study is devoted to the study of the prospects for the development of Kazakhstan’s foreign trade with the countries of the Comprehensive Regional Economic Partnership (CREP) by analyzing the indicators of the openness of the economy and the use of econometric forecasting models. The relevance of the work is due to the need to consider the prospects for the development of Kazakhstan’s foreign trade relations with the new trade association CREP for further formation of directions for the development of such relations based on the principles of evidence-based policy, since the results obtained in the study can serve as a basis for making public management decisions in the field of trade and customs policy. Within the framework of the article, the authors applied a strategy of combined research methods with a comparative analysis of the results of using each of them. Thus, econometric methods of Box-Jenkins forecasting, exponential smoothing with the use of tests to check their adequacy and validity were used. Forecast errors are calculated, such as the root-mean-square error, the average absolute error and the average absolute error as a percentage. The study resulted in forecasts of Kazakhstan’s foreign trade turnover with the CREP countries for the short term, which allowed us to conclude about the positive dynamics of the development of these trade relations. A more accurate forecast is presented based on the use of the exponential smoothing method, which demonstrates the smallest error size and is easier to apply.